Does employers’ perception and preferences play a significant impact on female employability? An empirical study in Perak, Malaysia - Ganapathy, Thavamalar; Abdul Jalil, Norasibah; Zakariya, Zainizam (International Business Education Journal, 2025)
The main purpose of this study is to identify the determinants of female labour force participation in Perak, Malaysia, from the employer’s perspective. The instrument used for data collection is a survey form, and the respondents who participated in this study are employers and human resource officers. A total of 72 respondents participated in this study through a stratified random sampling technique. A Binary Logistic Regression Model (BRM) is used to estimate the effects of the determinants on female labour force participation. Based on the results obtained, internship experience increases women’s employability by 68 times compared to those without such experience. In terms of employers’ gender, male employers are more likely (33 times) to hire female workers compared to female employers. The likelihood of female employment increases for applicants with self-reliance but decreases for those with significant responsibility at home. By identifying the contributing factors, the findings of this study are expected to provide information and guidelines to the related parties in their efforts to further improve women’s economic status.